Optimal Bank Reorganization Policies and the Pricing of Federal Deposit Insurance - ACHARYA, SANKARSHAN; DREYFUS, JEAN‐FRANCOIS (Journal of Finance, 1989)
ABSTRACT Optimal dynamic regulatory policies for closing ailing banks and for deposit insurance premia are derived as functions of the rate of flow of bank deposits, and interest rate on deposits, the economy's risk‐free interest rate, and the regulators' bank audit/administration costs. Under competitive conditions, the threshold assets‐to‐deposits ratio below which a bank should be optimally closed is shown to be greater than or equal to one. Optimal deposit insurance premia and probabilities of bank closure are shown to be nondecreasing in the bank's risk on investment and nonincreasing in the bank's current assets‐to‐deposits ratio.